Spectral tuning of light-harvesting complex II in the siphonous alga Bryopsis corticulans and its effect on energy transfer dynamics - Akhtar, Parveen (2021)
Light-harvesting complex II (LHCII) from the marine green macroalga Bryopsis corticulans is spectroscopically characterized to understand the structural and functional changes resulting from adaptation to intertidal environment. LHCII is homologous to its counterpart in land plants but has a different carotenoid and chlorophyll (Chl) composition. This is reflected in the steady-state absorption, fluorescence, linear dichroism, circular dichroism and anisotropic circular dichroism spectra. Time-resolved fluorescence and two-dimensional electronic spectroscopy were used to investigate the consequences of this adaptive change in the pigment composition on the excited-state dynamics. The complex contains additional Chl b spectral forms - absorbing at around 650 nm and 658 nm - and lacks the red-most Chl a forms compared with higher-plant LHCII. Similar to plant LHCII, energy transfer between Chls occurs on timescales from under hundred fs (mainly from Chl b to Chl a) to several picoseconds (mainly between Chl a pools). However, the presence of long-lived, weakly coupled Chl b and Chl a states leads to slower exciton equilibration in LHCII from B. corticulans. The finding demonstrates a trade-off between the enhanced absorption of blue-green light and the excitation migration time. However, the adaptive change does not result in a significant drop in the overall photochemical efficiency of Photosystem II. These results show that LHCII is a robust adaptable system whose spectral properties can be tuned to the environment for optimal light harvesting.